Investigation of viscoelastic effects on micro hot embossing process - Tan, Chin Jiat (2014)
In this research, a silicon tool was employed to emboss 1000 μm circular features on a poly(methyl methacrylate) (PMMA) sheet. The features were embossed at heating temperatures 105 oC to 125 oC and at different embossing forces ranging from 100 kg to 800 kg. The change in the dimensions of these features was noted at various time intervals. Features that were formed at heating temperatures of 125 oC and 115 oC showed viscoelastic effects, as the diameters recovered to a stable dimension over a period of one week. The depths of the features formed were also measured, but were not used to investigate the phenomenon of viscoelasticity due to the difficulty of measuring at the same point using a stylus profilometer. The readings of the depths were used to study the formation of shoulders around the circumference of the features embossed. It was shown that lower forces could not produce features of the required depth and could cause formation of shoulders. Too high an embossing force would produce shoulders due to stiction effects and an ideal force of 500 to 600 kg based on the height and number of shoulders formed was recommended.